2018
DOI: 10.3390/nu10091202
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Diagnosis of Magnesium Status

Abstract: Magnesium is a critical mineral in the human body and is involved in ~80% of known metabolic functions. It is currently estimated that 60% of adults do not achieve the average dietary intake (ADI) and 45% of Americans are magnesium deficient, a condition associated with disease states like hypertension, diabetes, and neurological disorders, to name a few. Magnesium deficiency can be attributed to common dietary practices, medications, and farming techniques, along with estimates that the mineral content of veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(157 citation statements)
references
References 175 publications
2
123
0
5
Order By: Relevance
“…18,19 Most epidemiological studies have defined concentrations below 0.70 mmol/L as "very low" 20 below 0.75 mmol/L as "low". However, there is ongoing debate as to the serum magnesium concentration threshold below which a patient may be considered to be deficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Most epidemiological studies have defined concentrations below 0.70 mmol/L as "very low" 20 below 0.75 mmol/L as "low". However, there is ongoing debate as to the serum magnesium concentration threshold below which a patient may be considered to be deficient.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is ongoing debate as to the serum magnesium concentration threshold below which a patient may be considered to be deficient. 18,19 Most epidemiological studies have defined concentrations below 0.70 mmol/L as "very low" 20 below 0.75 mmol/L as "low". 22,23 In the present study, approximately 65% of patients with AWS had low circulating concentration of magnesium (<0.75 mmol/L) and this was independently associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini dapat dikarenakan bahan makanan sumber serat seperti sayuran dan biji-bijian utuh merupakan sumber magnesium yang tinggi, sehingga peningkatan asupan serat berhubungan dengan peningkatan kadar magnesium. 21 Magnesium merupakan mineral yang berperan sebagai antioksidan dan kofaktor beberapa enzim yang dapat menjaga stabilitas membran dan mecegah stres oksidatif. 8 36 Selain recall 24 jam dan SQ-FFQ, penilaian asupan zat gizi makro juga bisa menggunakan metode food record dimana responden mencatat semua makanan yang dikonsumsi sehingga asupan zat gizi dalam sehari dapat diketahui.…”
Section: Hasil Dan Pembahasanunclassified
“…20 Selain itu pemeriksaan magnesium serum lebih banyak digunakan untuk menentukan status magnesium dalam tubuh dibandingkan dengan pengukuran magnesium pada urin, tinja atau jaringan lainnya dan dianggap reliabel untuk mewakili simpanan magnesium dalam tubuh. 21 Sampai saat ini pengukuran magnesium serum banyak dilakukan pada pasien Diabetes. Peneliti tertarik untuk menganalisis hubungan kadar magnesium bersama dengan variabel asupan energi dan zat gizi makro serta magnesium terhadap kadar glukosa darah puasa pada dewasa overweight dan obesitas di Kecamatan Serengan Kota Surakarta.…”
unclassified
“…Several studies show that Mg ingestion in the diet is below the recommended levels -it is estimated that 50-60% of adults do not reach the average dietary intake 18,19 . A growing body of evidence from epidemiologic and clinical studies has confirmed the association of magnesium deficiency with several diseases such as electrolyte, neurologic, musculoskeletal and inflammatory disorders; cardiovascular diseases and diabetes 15,20,21 .…”
Section: Introductionmentioning
confidence: 99%